Tracheal intubation with volatile induction and target bispectral index of 25 versus 40: A randomized clinical trial - Purva Khandelwal; Kanti Kumar Gombar; Vanita Ahuja; Satinder Gombar (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: A target bispectral index (BIS) value of 40 is considered adequate for depth of anesthesia, but no consensus exists regarding BIS value for tracheal intubation without neuromuscular blocking drugs. The aim of this randomized, double-blinded study was to compare the total duration from sevoflurane induction to tracheal intubation at a BIS value of 25 or 40. Material and Methods: This study was a prospective, randomized and observer-blinded clinical trial. After approval of the Institutional Ethics Committee and written informed consent, 80 patients of American Society of Anesthesiologists physical status I-II, aged 20-60 years, of either sex, requiring general anesthesia with tracheal intubation were enrolled. The patients were randomized to either Group BIS40-intubation at a target BIS value of 40 ± 5 or group BIS25-intubation at a target BIS value of 25 ± 5. The intubating conditions, hemodynamic, and adverse effects were observed in both the groups. Results: This study showed that the total time required from induction to tracheal intubation was 4.9 ± 0.9 min in group BIS40 as compared to 6.3 ± 0.5 min in group BIS25(P = 0.001) using two-tailed sample t-test. The mean intubation score was 6.5 ± 0.9 in group BIS40, and 5.1 ± 0.7 in group BIS25(P = 0.001) using Mann-Whitney U-test. Conclusion: The time to achieve target BIS value of 25 was greater as compared to target BIS value of 40 during sevoflurane induction but provided better intubating conditions in the absence of neuromuscular agents.